2006
DOI: 10.1007/s12015-006-0015-x
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical vein endothelial cells and human dermal microvascular endothelial cells offer new insights into the relationship between lipid metabolism and angiogenesis

Abstract: Human umbilical vein endothelial cells (HUVECs) have played a major role as a model system for the study of the regulation of endothelial cell function and the role of the endothelium in the response of the blood vessel wall to stretch, shear forces, and the development of atherosclerotic plaques and angiogenesis. Here, we use HUVECs and human microvascular endothelial cells to study the role of the HMG-CoA reductase inhibitor, simvastatin, and the small GTP-binding protein Rho in the regulation of angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
121
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(128 citation statements)
references
References 38 publications
1
121
1
Order By: Relevance
“…In terms of biological characteristics, HUVECs are similar to artery endothelial cells, and have been widely used as a model to study endothelial cell function (Park et al, 2006). In the present study, we showed that HG concentrations decreased viability of endothelial cells and increased their apoptosis, while lower concentrations had no effect.…”
Section: Discussionsupporting
confidence: 56%
“…In terms of biological characteristics, HUVECs are similar to artery endothelial cells, and have been widely used as a model to study endothelial cell function (Park et al, 2006). In the present study, we showed that HG concentrations decreased viability of endothelial cells and increased their apoptosis, while lower concentrations had no effect.…”
Section: Discussionsupporting
confidence: 56%
“…To study substrate-free SiNW endocytosis, human umbilical vascular endothelial cells (HUVECs) were selected as a model cell line. Because SiNWs can potentially be distributed in a drug-like fashion, endothelial cells would play a key role in mediating biointegration, with HUVECs, in particular, having been shown to recapitulate many of the features found in native vascular endothelial cells ( 31 ). …”
Section: Resultsmentioning
confidence: 99%
“…Endothelial cells respond to VEGF with mitogenesis, followed by the organization of cells into new vessels [57], [58]. To determine the anti-angiogenic potential of OMA, and its potential mechanism of action through VEGF inhibition, in vitro angiogenesis assays measuring proliferation, transmigration, and tube formation were performed in HUVECs.…”
Section: Resultsmentioning
confidence: 99%